Praktik Jual Beli Sawah dengan Sistem Ngemplong di Desa Karangjengkol Cilacap - Saifudin Saifudin; Muhajir Muhajir; Achmad Nursobah; Maolana Mujib (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Sale and purchase is the transfer of ownership rights between the seller and the buyer in absolute terms, either of the goods or benefits. In Karangjengkol Village, Kesugihan District, Cilacap Regency, there is a land sale and purchase using the Ngemplong system. Namely buying and selling by selling rice fields to buyers with conditions for the buyer. Usually the requirement is a certain time. This research is classified into the type of field research. Through an Islamic legal approach and using qualitative data analysis. The practice of buying and selling in Karangjengkol Village, Kesugihan District, Cilacap Regency is a practice of renting with the term ngemplong, seeing the terms and conditions of the lease, or the conditions for the goods being rented, which have been fulfilled. In terms of ‘urf, it is a habit in the form of speech (‘urf qaulῑ), and from the point of view of its scope, it is a general habit ('urf ᾱm). Meanwhile, in terms of its validity from the point of view of syara', it is a valid habit (‘urf sahῑh). And also meets the ‘urf requirements. So that the practice of leasing with the term buying and selling according to sharia, is legal and can be used.